Different mechanisms underlie the long‐term regulation of pyruvate dehydrogenase kinase (PDHK) by tri‐iodothyronine in heart and liver - Priestman, D; Donald, E; Holness, M; al., E (Wiley, 1997)
Antibodies to purified recombinant PDHKII were used for ELISAs of PDHKII in mitochondrial extracts. In liver, hyperthyroidism elicited a 2.3‐fold increase in PDHK activity (P<0.01) which was accompanied by a significant 1.5‐fold (P<0.001) increase in the amount of mitochondrial immunoreactive PDHKII. In contrast, despite a stable 2.0‐fold increase in cardiac PDHK activity (P<0.001), the amount of mitochondrial immunoreactive PDHKII in heart was unaffected by hyperthyroidism. The mechanisms for long‐term regulation of PDHK activity by thyroid hormones therefore differ fundamentally between heart and liver.